Travesía de la Esperanza La inmigración portuguesa en Barquisimeto (1948-1958) - Rodríguez, Froilán Ramos (Ariadna Ediciones, 2020)
The text is a balanced example of research and discursive synthesis. The first hundred pages, which correspond to the first two chapters, insert the reader into the context of both the mobility of the Portuguese and the conditions and circumstances of the corresponding migratory process, existing in both countries. However, the two following chapters show the unique and relevant contribution of Ramos Rodríguez to the history of immigration in Venezuela; very particularly, the author offers a multifaceted regional perspective of the larger process of Portuguese immigration.